Kelayakan Standar Sarana dan Prasarana SMK Kompetensi Keahlian DPIB di Kota dan Kabupaten Bekasi (Studi Kasus di SMKN 6 Kota Bekasi dan SMKN 1 Cikarang Barat) - M. Agphin Ramadhan; R. Eka Murtinugraha; Muhamad Subarkah (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
This study aims to determine the feasibility of facilities and infrastructure of the Building Information Modeling (DPIB) Skills Competency Vocational School in Bekasi City and Regency in terms of Permendikbud No. 34 of 2018 and the Vocational Practice Exam Vocational School Verification Instrument issued by the National Education Standards Agency (BSNP). This research is a descriptive research method with a quantitative approach. Research data collection through observation, documentation and interviews. The data analysis used was descriptive statistics. The results of this study indicate that the feasibility level of the facilities and infrastructure of the DPIB Skills Competency Vocational School in Bekasi City in this case is SMK Negeri 6 Bekasi City, namely for the feasibility of class room facilities and the feasibility of practical room facilities with very feasible categories, for the availability of classroom facilities, feasibility of infrastructure. Classrooms and the availability of practical room facilities are categorized as feasible, while the feasibility of practice room infrastructure is categorized as less feasible. The feasibility level of the DPIB Skills Competency Vocational School in Bekasi Regency, in this case SMK Negeri 1 Cikarang Barat, is the feasibility of class room facilities and the feasibility of practice room facilities is categorized as very feasible, for the availability of classroom facilities, the availability of practice room facilities and the feasibility of practice room infrastructure are categorized as feasible. , while the feasibility of practice room infrastructure is categorized as less feasible.